Umowa cywilnoprawna i porozumienie administracyjne jako formy działania organów administracji w sferze zarządzania gospodarką państwową - Kmieciak, Zbigniew (Wydział Prawa i Administracji UAM, 1987)
The realization of the management tasks by the administrative agencies in conditions of a decentralized model of the economy requires the tools adjusted to the wide range of self-dependence of enterprises. The instruments which undoubtedly meet the above requirements are a civil law contract and an administrative agreement. The author has carried out the analysis of the said acts defining their characteristic features and pointing out to the differences between the two insruments. According to the author, common features of both acts are relatively equal status of participants (parties) and their unanimous expression of the will to conclude an act on cooperation. In the author's opinion, the law in force seems to point out to the tendency of a further development of a civil law contract and an administrative agreement as forms of the administrative agencies' activity in the management of the state economy. He indicates that the appearance of new types of bilateral acts and the transformation of the traditional ones is a natural course for the evolution of legal forms of the administrative activity. He stresses the need to work out a consistent conception, expressed in legal norms, of applying those acts by the administrative agencies. He presented some elements of such a conception and formulated some postulates as to the future law. Finally, he is against an excessively detailed legal regulation of the said instruments.
A civil-law contract and an administrative agreement as forms of the administrative agencies' activity in the management of the state economy